Fluid Balance Variations During the Early Phase of Large Hemispheric Stroke Are Associated With Patients' Functional Outcome - Pelz, Johann Otto; Fischer, Marie-Michéle; Bungert-Kahl, Peggy; Lindner, Dirk; Fricke, Christopher; Michalski, Dominik (Frontiers in Neurology, 2019)
Background: From the variety of factors underlying the ischemia-associated edema formation in large hemispheric stroke (LHS), an increased brain water content during the early phase seems to have a pivotal role for long-lasting tissue damage. However, the importance of the fluid management during the acute phase of LHS has so far not been adequately studied. Therefore, this study explored the association between the fluid balance and functional outcome in patients suffering from LHS. Methods: We analysed hospital-based medical records of 39 consecutive patients with LHS and decompressive hemicraniectomy. Over the first 10 days after admission, the volumes of all administered fluids were assessed daily and corrected for daily urinary output and insensible loss. Functional outcome at 3 months was assessed with the modified Rankin Scale (mRS) and dichotomized into an acceptable (mRS ≤ 4) versus a poor outcome (mRS ≥5). Results: Compared to patients with a poor functional outcome (n=19), those with an acceptable outcome (n=20) were characterized by a significantly lower cumulative net fluid balance at day 5 (1.6±2.5 vs. 3.4±4.4 l), day 7 (2.0±2.9 vs. 4.6±5.2 l) and day 10 (0±2.5 vs. 5.6±6.2 l). In addition to age, only the cumulative net fluid balance at day 10 served as an independent factor for poor functional outcome in multiple regression analyses. Conclusion: These data provide evidence for a critical role of the early phase net fluid balance with respect to the functional outcome after LHS. This observation leads to the hypothesis that patients with LHS might benefit from a more restrictive volume therapy. However, prospective studies are warranted to establish a causal relationship and recommendations for treatment strategies.